SIMULASI VIDEO MENGGAMBAR AUTOCAD UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK BISNIS KONSTRUKSI DAN PROPERTI - Muh. Jasrin Sarif; Anas Arfandi; Tri Pancayana (Jurnal Education, 2024)
This study applies the Classroom Action Research (CAR) method to integrate AutoCAD video simulation into Technical Drawing learning in the 10th grade of Business Construction and Property at SMK Negeri 3 Makassar. Data analysis includes descriptive and quantitative analysis. The research cycle comprises planning, action, observation, and evaluation/reflection. The integration of AutoCAD video simulation yields a significant improvement in learning outcomes, from 73% in the pre-cycle, 78% in cycle 1, to 84% in cycle 2. By the end of the cycle, the majority of students (79%) achieve scores above the Minimum Completeness Criteria (KKM). Adjustment of devices and simplification of materials help overcome technical constraints. The implementation of AutoCAD video simulation proves effective in enhancing Technical Drawing learning outcomes.